Analisis Numerik Dampak Pembangunan Jetty terhadap Dinamika Morfologi di Muara Sungai Jeneberang dengan Model Delft3D - Israil; Hamzah Al Imran; Muhammad Nur Fikry; Ahmad Rizky Sahabudin (Jurnal Karajata Engineering, 2026)
The Jeneberang River plays a vital role in flood control for Makassar City and Gowa Regency. However, it faces severe sedimentation problems following the landslide at Mount Bawakaraeng, which released approximately 200 million m³ of mud and sand into downstream areas. Sedimentation at the estuary reduces the river’s discharge capacity to the sea and significantly disrupts fishing vessel accessibility in the Tanjung Bunga area. This study aims to analyze coastal morphological dynamics and evaluate the effectiveness of jetty construction in controlling sediment accumulation using numerical simulations with Delft3D. The data employed include bathymetry, tides, currents, and sediment characteristics obtained from BMKG and Ina-Geoportal. Simulation results indicate substantial sediment buildup at the estuary prior to jetty construction. After the jetty was introduced, sediment concentration at the river mouth decreased markedly from 1.4 kg/m³ to 0.16 kg/m³ by the end of the simulation period. Morphologically, the jetty reduces current energy and alters sediment transport pathways, thereby maintaining the stability of the navigation channel. The novelty of this study lies in its quantitative evaluation of jetty effectiveness under extreme sediment supply conditions caused by large-scale upstream landslides, providing numerical-based evidence for jetty performance in highly sediment-laden estuaries. These findings confirm that jetty construction is an effective engineering solution to sustain navigation channels and support the continuity of local fishing activities.